The Socrates express : in search of life lessons from dead philosophers - Weiner, Eric, 1963- (Avid Reader Press, 2020)
Retraces the journeys of forefront intellectuals from Epicurus and Gandhi to Thoreau and Beauvoir to illuminate how their practical and spiritual lessons can be applied in today's unsettled world.